The impact of information technology on professional behavior in the field of human resources in Tehran governor - Rahim Ghorbani; Sara Ahangar (مطالعات مدیریت کسب و کار هوشمند, 2014)
Information technology and professional conduct are the themes that had effected the Iranian's organizations .And although there had been lots of researches all over the world ,but little tentative inquiries about their relations to eachother are done,paticularly effect of information technology on professional conduct of human resources .such researches analyse effect of professional conduct on human resources of the Tehran governor. This research is the combination of library and field research.Method of research in this study is "quantitative" or "serveying" techniques. And also based on the aim it perches on "applied" reseach group .it should be said that in this research yheinformations was gathered by questionaires. Based on the results gained by this research ,information technology has different effects on various indexes of human resources .It means that information technology increases the extend respond independent information and relations out of organization ,but using information technology has not any considerable effect on important activities.